Faktor-faktor yang Memengaruhi Keputusan Konsumen dalam Membeli Kopi di Nurona Space Bandung - Khairunnisa, Afifa; Wiyono, Sulistyodewi Nur; Sulistyowati, Lies; Rachmawati, Erna (Universitas Galuh, 2024)
The rapid growth of local coffee shops in Bandung has required Nurona Space to get to know its customers. However, in the midst of the rapid growth of the local coffee industry, the biggest challenge faced by Nurona Space is fluctuating sales, which can disrupt the stability of its business. The study aims to describe the characteristics of consumers who purchase coffee and analyze the factors that influence consumer decisions on coffee purchases at Nurona Space Bandung. This study uses a quantitative design with a sample of 120 people taken using accidental sampling technique. The data analysis technique used by researchers is descriptive analysis and factor analysis. Based on the results of the study, it shows that there are seven new factors that influence consumer decisions in buying coffee at Nurona Space, namely, service quality factors, word of mouth, physical evidence, store atmosphere, product prices, product assurance and quality, and reliability and trust. In this study, service quality is one of the most dominant factors in influencing purchasing decisions because it has an eigenvalue of 8.324 and explains 30.829 variations.